2021
DOI: 10.3390/nu13020300
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Change in Dietary Habits and Physical Activity during Lockdown in Spain Due to the COVID-19 Pandemic

Abstract: Background: Lockdown due to COVID-19 influenced food habits and lifestyles with potential negative health impact. This study aims to identify patterns of change in eating habits and physical activity during COVID-19 lockdown in Spain and to identify associations with sociodemographic factors and usual habits. Methods: This cross-sectional study included 1155 adults recruited online to answer a 10-section questionnaire. The protocol assessed usual diet by means of a semi-quantitative food frequency questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 51 publications
13
81
0
16
Order By: Relevance
“…Appetizer purchases nearly doubled between January (12.8 g/person/day) and April 2020 (22.1 g/person/day), in contrast to the same period of 2019, when they remained constant (January 12.2 g and April 13.8 g/person/day). An increase in the consumption of appetizers was also observed in other Spanish studies carried out during the lockdown [ 19 ], as well as in other countries such as Poland [ 31 ], Italy [ 12 ] or France [ 32 ], although other studies found no change or even decreases [ 33 ]. This increment in the purchase of appetizers is probably due to the desire to continue with some socialization habits that people did outdoors before the pandemic [ 28 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Appetizer purchases nearly doubled between January (12.8 g/person/day) and April 2020 (22.1 g/person/day), in contrast to the same period of 2019, when they remained constant (January 12.2 g and April 13.8 g/person/day). An increase in the consumption of appetizers was also observed in other Spanish studies carried out during the lockdown [ 19 ], as well as in other countries such as Poland [ 31 ], Italy [ 12 ] or France [ 32 ], although other studies found no change or even decreases [ 33 ]. This increment in the purchase of appetizers is probably due to the desire to continue with some socialization habits that people did outdoors before the pandemic [ 28 ].…”
Section: Discussionsupporting
confidence: 64%
“…Changes in eating habits were also observed in other European countries, such as Italy [ 11 , 12 , 13 ], Poland [ 14 , 15 ], Denmark [ 16 ], Germany, Slovenia [ 8 ], Ireland and Great Britain [ 17 ]. Although the reasons for these changes are still not fully understood, some authors have suggested that personal characteristics may modulate them, shaping different patterns of change [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the possibility exists that the main sampling method employed in the present study (ie web‐based questionnaire) has generated biased results, which can be only representative of people using social networks, rather than of the general public. Web‐based questionnaires, however, have been largely used to assess various health effects linked with the lockdown in European countries 41,42,52‐59 . In addition, a recent study exploring the psychological impact of the pandemic and lockdown measures in subjects from seven different countries showed that a moderate use of the social networks (ie 1‐2 hours per day) was linked with less negative effects, as compared with excessive use or no use at all.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies carried out in different countries have reported modification in alimentary profiles associated with the lockdown. In particular, increased consumption of foods with high sugar content, such as chocolate and salty snacks, has been reported [32,33]. The possible explanation of these alimentary regimen changes can be explained to the increased levels of anxiety and the difficulties to find open grocery stores close to home [34].…”
Section: Discussionmentioning
confidence: 99%